INNOVATIVE METHODS OF MANAGING CORPORATE CULTURE IN GLOBAL COMPANIES (World Bulletin of Management and Law, 2025)
The article analyzes innovative methods of corporate culture management in transnational corporations. The main emphasis is placed on the study of the influence of digital technologies, big data analytics, gamification and hybrid forms of employment on the formation of value orientations and normative regulators in the organizational environment. The study analyzes key barriers to the implementation of innovative approaches. In conclusion, recommendations are offered for overcoming the identified obstacles, including the development of digital literacy, localization of cultural strategies and the use of change management models.
Keywords: corporate culture; innovative management methods; global companies